2012
DOI: 10.1103/physrevlett.109.133201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of theS(D21)+HD(j=0

Abstract: We report integral cross sections for the Sð 1 D 2 Þ þ HDðj ¼ 0Þ ! DS þ H and HS þ D reaction channels obtained through crossed-beam experiments reaching collision energies as low as 0.46 meV and from adiabatic time-independent quantum-mechanical calculations. While good overall agreement with experiment at energies above 10 meV is observed, neither the product channel branching ratio nor the low-energy resonancelike features in the HS þ D channel can be theoretically reproduced. A nonadiabatic treatment emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…In recent years, the field of cold and ultra-cold chemistry has seen a considerable growth becoming a frontier both for applied and theoretical research in physics and chemistry (see e.g., Smith, 2008; Krems et al, 2009; Balakrishnan, 2016). The interested reader is directed to the recent review articles (Herschbach, 2009; Hutzler et al, 2012; Quemener and Julienne, 2012; van de Meerakker et al, 2012) for a detailed description of experimental and theoretical developments of the field of cold and ultra-cold molecules, and to (Lara et al, 2012; Tizniti et al, 2014; Costes and Naulin, 2016) for progress on chemical reactivity at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the field of cold and ultra-cold chemistry has seen a considerable growth becoming a frontier both for applied and theoretical research in physics and chemistry (see e.g., Smith, 2008; Krems et al, 2009; Balakrishnan, 2016). The interested reader is directed to the recent review articles (Herschbach, 2009; Hutzler et al, 2012; Quemener and Julienne, 2012; van de Meerakker et al, 2012) for a detailed description of experimental and theoretical developments of the field of cold and ultra-cold molecules, and to (Lara et al, 2012; Tizniti et al, 2014; Costes and Naulin, 2016) for progress on chemical reactivity at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, small beam intersection angle and low velocities for both beams are needed for attaining low collision energies in crossed beam experiments. Using this technique, Lara et al 98 reported experimental and theoretical studies of the S( 1 D 2 ) + HD ( j = 0) reaction at energies ranging from 0.46 meV to 54.2 meV. Explicit measurements of integral cross sections for the HS + D and DS + H products and their branching ratios were compared with time-independent coupled channel quantum calculations.…”
Section: Experimental Studies Of Cold and Ultracold Reactions Andmentioning
confidence: 99%
“…From the comparison of their results with the previous ones using Ho PES, they found that this surface gives a smaller cross section than the Ho PES, due to an unphysical barrier on the former PES. Subsequently, using TIQM calculations and crossed‐beam experiment, Lara et al studied the integral cross sections of S(1D)+normalH2/HD reactions in a very lower energy. They pointed out that because only a few partial waves contribute to the excitation function, their experimental results are consistent with the theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%